Ultrasonographic Tissue Perfusion in Peri-implant Health and Disease. (March 2022) - Barootchi, S.; Tavelli, L.; Majzoub, J.; Chan, H.L.; Wang, H.L.; Kripfgans, O.D.
Color flow ultrasonography has played a crucial role in medicine for its ability to assess dynamic tissue perfusion and blood flow variations as an indicator of a pathologic condition. While this feature of ultrasound is routinely employed in various medical fields, its intraoral application for the assessment of tissue perfusion at diseased versus healthy dental implants has never been explored. We tested the hypothesis that quantified tissue perfusion of power Doppler ultrasonography correlates with the clinically assessed inflammation of dental implants. Specifically, we designed a discordant-matched case-control study in which patients with nonadjacent dental implants with different clinical diagnoses (healthy, peri-implant mucositis, or peri-implantitis) were scanned and analyzed with real-time ultrasonography. Forty-two posterior implants in 21 patients were included. Ultrasound scans were obtained at the implant regions of midbuccal, mesial/distal (averaged as interproximal), and transverse to compute the velocity- and power-weighted color pixel density from color velocity (CV) and color power (CP), respectively. Linear mixed effect models were then used to assess the relationship between the clinical diagnoses and ultrasound CV and CP. Overall, the results strongly suggested that ultrasound's quantified CV and CP directly correlate with the clinical diagnosis of dental implants at health, peri-implant mucositis, and peri-implantitis. This study showed for the first time that ultrasound color flow can be applicable in the diagnosis of peri-implant disease and can act as a valuable tool for evaluating the degree of clinical inflammation at implant sites.